Pengaruh Asimetri Informasi, Budaya Organisasi dan Implementasi Good Governance terhadap Kecurangan Akuntansi - Muhammad Fazli; Vince Ratnawati; Azwir Nasir (Politeknik Ganesha Medan, 2023)
The purpose of this study was to determine the effect of Information Asymmetry, Organizational Culture, Implementation of Good Governance on the dependent variable of Accounting Fraud with Internal Control as a moderating variable. The population in this study was 46 OPD in Bengkalis Regency and the number of samples studied were 46 OPD in Bengkalis Regency with a total of 138 people. The data source is the primary data from the questionnaire. Variables are measured with a 5 point Likert scale. The data collection method is Structural Equation Modeling Partial Least Square (SEM-PLS) using WarpPLS software version 5.0. The results show that Information Asymmetry has a positive effect on Accounting Fraud, Organizational Culture and Implementation of Good Governance have a negative effect on Accounting Fraud, Internal Control weakens the positive effect of Information Asymmetry on Accounting Fraud, and Internal Control strengthens the influence of Organizational Culture and implementation of Good Governance on Accounting Fraud. The implementation of Good Governance directly has a negative effect on fraud, with the existence of a negative influence between the implementation of Good Governance on fraud, the implementation of internal control is able to strengthen the level of negative influence between the implementation of Good Governance on fraudulent acts that occur.